Penerapan Verzet terhadap Putusan Verstek dalam Praktik Peradilan Perdata - Maria Hera Agathea Manik; Andita Amelia; Anggi Sri Haryati Simarmata (CV. ITTC INDONESIA, 2026)
This study examines the legal framework and implementation of verzet as a legal remedy against verstek decisions in civil procedural law. The main issues addressed are the regulation of verzet, its procedural mechanism, and its legal consequences in judicial practice. The research aims to analyze the application of verzet and evaluate its effectiveness in ensuring fairness and legal certainty. This research uses a normative juridical method with statute and conceptual approaches, relying on secondary data obtained through library research, including legal literature, legislation, and court decisions. The results indicate that verzet serves as an essential legal instrument to protect the rights of defendants who were absent during trial. However, its implementation still faces several challenges, such as lack of legal awareness, improper summons procedures, short filing deadlines, and inconsistent judicial interpretations. These issues affect legal certainty, justice, and judicial efficiency. Therefore, improvements are needed through better public legal education, proper procedural enforcement, and consistent judicial application to optimize the function of verzet in civil justice.